Multimedia Data Secure Transmission: A Review (International Journal of Scientific Research and Management (IJSRM), 2022)
Encryption is a technique of encoding data so that they can only be recognized by authorized receivers. More interactive media information is communicated in the medical, business, and military fields because of the rapid advances in various multimedia transmission and networking technologies, which may contain sensitive information that must be kept hidden from public users. Advanced encryption standards (AES) and data encryption standards (DES) are widely used encryption algorithms for text data. However, they are not appropriate for video data. To ensure that this information cannot be accessed by attackers, the demand for efficient video-protection techniques has been raised. This article provides multimedia design requirements to maintain a secure multimedia system occupied with a threat model for detecting and ranking the potential risks facing a multimedia system. the risks exposed to multimedia security and their impacts on users are typically described according to the textual description and also an overview of the current state-of-the-art video-encryption schemes are presented and their performance parameters have been examined. The relationship between encryption algorithms and compression techniques is also discussed and various multimedia applications have been presented in this paper; Additionally, as the synchronisation of real-time continuous streams is necessary for the interchange of these streams in multimedia conferencing services, multiple synchronisation strategies have been given in this study along with video synchronisation challenges.